Keabsahan Akta Jual Beli Letter C Yang Diterbitkan Oleh Pejabat Pembuat Akta Tanah - Daniel, Glenn; Hadiati, Mia (Universitas Semarang, 2025)
This study seeks to investigate and acquire insights regarding the legal validity of the sale and purchase deed associated with Letter C and the impact of land erosion on land rights owners. The foundation of this research stems from the transaction involving the deed of sale and purchase of Letter C, carried out by the Land Deed Official, who overlooked the measurement of the Letter C land when transferring rights from one person to another. The significance of this research lies in addressing the issues that arise in various places in the archipelago are increasingly complex and increasingly varied, especially regarding the ownership of land rights with Letter C status, which do not have legal certainty over their ownership rights. This research employs the Normative Juridical approach, which analyzes literature documents and related regulations while emphasizing the duties and permits of PPAT, so that it will provide the right answers regarding land rights problems and literacy to the community regarding land rights ownership. The results of this study explain that Letter C land sale and purchase transactions that are not accompanied by measurements and are not immediately certified have the potential to cause disputes and difficulties in proving land rights because there are legal loopholes, so owners must confirm the validity of ownership of land rights. The novelty of this research lies in the analysis of cases that occurred in Bogor Regency, illustrating the consequences of the incident, so that it can provide a solution so that the Letter C land that is still circulating in the community can immediately change its land rights status to provide security in land ownership. Penelitian ini bertujuan untuk menggali serta mendapatkan pengetahuan tentang keabsahan akta jual beli Letter C serta dampak dari terkikisnya tanah bagi pemilik hak atas tanah. Dasar penelitian ini berasal dari transaksi akta jual Beli Letter C yang disusun oleh Pejabat Pembuat Akta Tanah (PPAT) tanpa memperhatikan pengukuran tanah Letter C yang dialihkan haknya dari satu individu ke individu lainnya. Urgensi dari penelitian ini adalah permasalahan yang terjadi diberbagai tempat di Nusantara semakin kompleks dan semakin variatif khususnya tentang kepemilikan hak atas tanah yang berstatus Letter C yang tidak mendapatkan kepastian hukum atas hak kepemilikannya. Penelitian ini menerapkan metode Yuridis Normatif dengan menganalisis dokumen literatur dan peraturan yang relevan serta memperjelas tugas dan kewenangan PPAT, sehingga penelitian ini akan memberikan jawaban yang tepat mengenai permasalahan hak atas tanah serta meningkatkan literasi terkait kepemilikan hak atas tanah kepada masyarakat. Temuan dari penelitian ini menunjukkan bahwa kegiatan jual beli tanah Letter C yang tidak disertai pengukuran dan tidak segera disertifikatkan berpotensi menyebabkan sengketa serta kesulitan pembuktian hak atas tanah karena terdapat celah hukum, sehingga pemilik harus mempertegas validitas kepemilikan hak atas tanah. Kebaruan dalam penelitian ini dijelaskan dalam analisis dari kasus yang terjadi di Kabupaten Bogor yang menjabarkan dampak dari peristiwa tersebut, sehingga dapat memberikan solusi agar tanah Letter C yang masih beredar dalam masyarakat segera diubah status hak atas tanahnya untuk memberikan keamanan dalam kepemilikan tanah.